Exploring the foreign language effect in bi and multilinguals - Olsson, Sebastian (Luleå tekniska universitet, Institutionen för hälsa, lärande och teknik, 2023)
Would your decision-making be different if you used your foreign language? This is a topic that has gained attention in the field of cognitive psychology in recent years. Work today often involves two or more languages and at times requiring processing of information in a language that is not ones native. This raises a question; does use of a foreign language influence reasoning? The study aims to explore how a foreign language affects reasoning in a bi and multilingual population, looking specifically at age of acquisition, which order participants rank their foreign language and if linguistic distance has associations to performance on a reasoning task. The present study examines fifty Swedish bi and multilingual participants with the languages English and Meänkieli. Unequal years of education makes the results of the reasoning task inconclusive. A possible relationship with the order and age of acquisition, and linguistic distance could be found. Overall, results suggest further research is needed to explore the variables in detail.